2014
DOI: 10.1158/2326-6066.cir-14-0093-t
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy Promotes Indirect Elimination of Intraocular Tumors by CD8+ T Cells That Is Associated with IFNγ- and Fas/FasL-Dependent Activation of Intratumoral Macrophages

Abstract: Ocular immune privilege (IP) limits immune surveillance of intraocular tumors as certain immunogenic tumor cell lines (P815, E.G7-OVA) that are rejected when transplanted in the skin grow progressively when placed in the anterior chamber (a.c.) of the eye. As splenectomy (SPLNX) is known to terminate ocular IP, we characterized immune mechanisms responsible for rejection of intraocular tumors in SPLNX mice as a first step toward identifying how to restore tumoricidal activity within the eye. CD8+ T cells, IFNγ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Importantly, these observations suggest that the distant environment (the spleen in this case) can represent a useful therapeutic target to affect primary tumour progression. Similar findings were reported in other cancer types . Along these lines, increased risk of malignancies has been observed in follow‐up studies of patients subjected to splenectomy .…”
Section: The Key Role Of the Toesupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, these observations suggest that the distant environment (the spleen in this case) can represent a useful therapeutic target to affect primary tumour progression. Similar findings were reported in other cancer types . Along these lines, increased risk of malignancies has been observed in follow‐up studies of patients subjected to splenectomy .…”
Section: The Key Role Of the Toesupporting
confidence: 84%
“…Similar findings were reported in other cancer types. 29,30 Along these lines, increased risk of malignancies has been observed in follow-up studies of patients subjected to splenectomy. 31,32 Of note, in some reports, a tumour-promoting effects of splenectomy has been observed, associated with increased number of FoxP3 + regulatory T cells at the metastatic sites.…”
Section: The Key Role Of the Toementioning
confidence: 97%
“…4 However, we demonstrated that CD4 C T cells were not required for rejection of intraocular tumors; 2 rather, CD8 C T cells were indispensable. 2 The simplest explanation for how the spleen limits immunosurveillance of intraocular tumors is that CD8 C T-cell tolerance to tumor antigens arises in the spleen, which is supported by our previous study indicating that introduction of soluble antigens into the anterior chamber induced expansion but functional inactivation of antigen-specific CD8 C T cells. 5 However, we and others have shown that intraocular tumor growth does not induce systemic CD8 C T-cell tolerance.…”
mentioning
confidence: 78%
“…1) but not perforin or TNFa. 2 IFNg and FasL did not target tumor cells directly as SPLNX IFNgR1 ¡/¡ and Fas-defective lpr mice failed to eliminate intraocular tumors that expressed IFNgR1 and Fas. 2 Bone marrow chimeric mice indicated that rejection of intraocular tumors in SPLNX mice required IFNgR1 and Fas expression on immune cells, and SPLNX increased the frequency of activated macrophages within intraocular tumors in an IFNg and Fas/FasL-dependent manner suggesting a cellular target for IFNg and FasL.…”
mentioning
confidence: 99%
See 1 more Smart Citation